DEVELOPMENT OF HUMAN RESOURCES IN ISLAMIC EDUCATIONAL INSTITUTIONS - Nurul Indana; Sokip Sokip; Asrop Syafi’I (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2023)
Human resources in educational institutions is a management sub-system that needs to receive the same attention as other management sub-systems, because it is the key to educational success. This research uses library research methods, with documentary data collection techniques and analysis using content analysis. The research results state that human resource development is an effort to develop quality through the process of planning education, training and managing personnel or employees to achieve optimal results. Islamic education will be affected, therefore Islamic education must be able to survive in order to be successful in 21st century competition. Human Resources Human Resources Development emphasizes increasing the ability to carry out future tasks. The development method consists of:on the job, vestibule, demonstration and example, simulation, apprenticeship, dan classroom methods. There are five strategies for Islamic education institutions in building Muslim human resources with superior characteristics: optimizing the role of Islamic education institutions, upgrading the competence of teachers and lecturers in educating and teaching, reviewing and developing competency and character-based curricula and reconstructing the learning environment and academic culture.